A biblical theology of youth ministry : teenagers in the life of the church - McGarry, Mike, 1980-; Mueller, Walt, 1956- (Nashville Randall house publications, 2019)
"Youth ministry today has fallen on hard times. Many churches continue to employ the same methods that have become entrenched over the last few decades, while others are questioning the need for youth ministry at all. Michael McGarry explores the foundation of youth ministry in the Old and New Testaments and brings that together with Church history in a compelling way. This contemplative and well-researched book provides a careful critique of youth ministry along with practical guidance for those serving in ministry. The author directs the reader toward a new era of youth ministry where parents and intergenerational ministry play a more significant role. McGarry shares five pillars of gospel-centered youth ministry and reminds readers of the spiritual priority of parents. This work includes an excellent list of essential building blocks for youth ministry along with practical advice for creating a bridge-building ministry connecting church and home."--Amazon.com.
Minimal Level Cataloging Plus.
Keywords: Church work with teenagers; Christian education of teenagers